2014
DOI: 10.1177/1471301214561532
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a baby doll therapy protocol for people with dementia: Innovative practice

Abstract: Dementia is exhibited by both emotional and physical states such as agitation. Chemical restraints, often used for agitated behaviors, are not always effective and produce untoward effects. Baby doll therapy is a nonpharmacologic therapy that can affect agitated behavior in dementia patients, yet a protocol for the therapy did not exist. An implementation protocol for doll therapy for those with dementia was developed and implemented with 16 residents in a dementia care center. Outcomes were measurements of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
20

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 4 publications
0
25
0
20
Order By: Relevance
“…Twelve articles assessed as having medium to strong quality evidence were identified using the search term 'doll' (mean REA score = 19.5, strong). Despite some staff and family members viewing dolls as patronising or infantilising (Hubbard & Olsen, 2016;Braden & Gaspar, 2015;Shin, 2015;Hahn, 2015;Mitchell & Templeton, 2014;James, Mackenzie, & Mukaetova-Ladinska, 2006;Alander, Prescott, & James, 2015), all 12 articles agreed regarding the positive impact of offering dolls to care home residents with dementia, including: improved communication and social interaction (Ng, Ho, Koh, Tan, & Chan, 2017;Mitchell, McCormack, and McCance, 2016;Alander et al 2015;Shin, 2015;Bisiani & Angus, 2013;Cohen-Mansfield, Marx, Dakheel-Ali, Regier, and Thein, 2010); reduced anxiety (Alander et al 2015;Bisiani & Angus, 2013); and reduction in behavioural and psychological symptoms of dementia (Cantarella, Borella, Faggian, Navuzzi, & De Beni, 2018). Mitchell et al (2016) reported an improvement in eating, however, Cantarella et al (2018) did not.…”
Section: Dollsmentioning
confidence: 99%
“…Twelve articles assessed as having medium to strong quality evidence were identified using the search term 'doll' (mean REA score = 19.5, strong). Despite some staff and family members viewing dolls as patronising or infantilising (Hubbard & Olsen, 2016;Braden & Gaspar, 2015;Shin, 2015;Hahn, 2015;Mitchell & Templeton, 2014;James, Mackenzie, & Mukaetova-Ladinska, 2006;Alander, Prescott, & James, 2015), all 12 articles agreed regarding the positive impact of offering dolls to care home residents with dementia, including: improved communication and social interaction (Ng, Ho, Koh, Tan, & Chan, 2017;Mitchell, McCormack, and McCance, 2016;Alander et al 2015;Shin, 2015;Bisiani & Angus, 2013;Cohen-Mansfield, Marx, Dakheel-Ali, Regier, and Thein, 2010); reduced anxiety (Alander et al 2015;Bisiani & Angus, 2013); and reduction in behavioural and psychological symptoms of dementia (Cantarella, Borella, Faggian, Navuzzi, & De Beni, 2018). Mitchell et al (2016) reported an improvement in eating, however, Cantarella et al (2018) did not.…”
Section: Dollsmentioning
confidence: 99%
“…In spite of the benefits, the use of therapeutic dolls also has its negatives, such as the infantilization of the senior, thereby breaking ethics. For these reasons, we must emphasize the individual approach and we cannot generalize their mass use under any circumstances [24].…”
Section: Doll Therapymentioning
confidence: 99%
“…Ugotovili so, da se je interakcija z negovalnim osebjem izboljšala. Manj je bilo tesnobe, tavanja, nemira, agresivnega vedenja in halucinacij (James, et al, 2006;Braden & Gaspar, 2015). Z vidika zadovoljevanja duhovnih potreb oseb, obolelih za demenco, so nefarmakološki pristopi zelo pomembni.…”
Section: Uvodunclassified
“…Z vidika zadovoljevanja duhovnih potreb oseb, obolelih za demenco, so nefarmakološki pristopi zelo pomembni. Različne raziskave (James, et al, 2006;Bisiani & Angus, 2012;Mitchell & Templeton, 2014;Pezzati, et al, 2014;Braden & Gaspar, 2015) ugotavljajo, da je terapija z lutko v holistični obravnavi oseb, obolelih za demenco, zelo učinkovita. Glede na hitro naraščanje števila oseb, obolelih za demenco, je poznavanje terapije z lutko kot načina zmanjševanja vedenjskih, psiholoških sprememb in duhovne stiske lahko priložnost za njeno vključitev v obravnavo oseb z demenco tudi v slovenskem prostoru.…”
Section: Uvodunclassified